2021
DOI: 10.5040/9781350088276
|View full text |Cite
|
Sign up to set email alerts
|

Low-Fee Private Schooling and Poverty in Developing Countries

Abstract: In Low-fee Private Schooling and Poverty in Developing Countries Joanna Härmä draws on primary research carried out in Sub-Saharan African countries and in India to show how the poor are being failed by both government and private schools. The primary research is combined with additional examples from around the world to offer a wide perspective on the issue of marketized education, low-fee private schooling and government systems. Härmä offers a pragmatic approach to a divisive and ideologically-driven issue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 0 publications
1
20
0
1
Order By: Relevance
“…The growing pressure caused by both forces has prompted school owners to seek long-term financing to expand and meet that demand. It has also fueled an expansion of low-fee schools (Härmä 2021). Yet in many countries, financing can be difficult to obtain and then only at onerous rates.…”
Section: Private Sector Investmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The growing pressure caused by both forces has prompted school owners to seek long-term financing to expand and meet that demand. It has also fueled an expansion of low-fee schools (Härmä 2021). Yet in many countries, financing can be difficult to obtain and then only at onerous rates.…”
Section: Private Sector Investmentmentioning
confidence: 99%
“…The small size and relative business-related immaturity of many K-12 private schools, particularly low-fee private schools, inhibit their scalability. Operators of low-fee private schools often have no financial training, lack access to capital, and rely on a single, uncertain revenue stream: tuition payments(Härmä 2021; Results for Development 2016). Because these small businesses cannot absorb large investments, private equity investments are rare and tend to be from local sources when they do occur.…”
mentioning
confidence: 99%
“…While debate rages regarding the desirability of this trend, individual school proprietors in ever-growing numbers go about their daily business of providing education after a fashion. It is now widely accepted that these schools exist, for better or for worse, and the debate moved on some years ago to whether these schools were providing reasonable quality (Härmä, 2021). Now questions swirl about their contribution to the achievement of Sustainable Development Goal 4 (UNESCO, 2021), something the proprietors themselves likely are not much concerned about.…”
Section: Introductionmentioning
confidence: 99%
“…This article does not go in depth into questions of pedagogy or teacher training for the teaching of mathematics -these are questions for other articles in this volume. This article will consider the current situation of teaching mathematics in LFP schools in SSA drawing in particular on studies from Kenya, Ghana and Nigeria, and also on my many personal experiences in observing lessons in such schools during research studies on their incidence, costs and accessibility (my work can be found at www.joannaharma.net and in Härmä, 2021). The next section will provide some background on low-fee private schooling in sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation